An Insight into the Interactions between α-Tocopherol and Chitosan in Ultrasound-Prepared Nanoparticles. (27th June 2010) - Naghibzadeh, Majid; Amani, Amir; Amini, Mohsen; Esmaeilzadeh, Elina; Mottaghi-Dastjerdi, Negar; Faramarzi, Mohammad Ali
Abstract : The aim of this study was to investigate the interactions betweenα -tocopherol and chitosan molecules prepared subsequent to preparation ofα -tocopherol-loaded chitosan nanoparticles using ultrasonication. Dynamic light scattering (DLS) and scanning electron microscopy (SEM) analyses showed semispherical particles with an average size of approximately 350 nm. Also from reconstitution test, α -tocopherol was suggested as stabilizing agent during lyophilization/reconstitution process. The zeta potentials of chitosan andα -tocopherol nanoparticles were larger than± 30 mV, representing suitable stability. Data obtained from FTIR showed possibility of chemical interaction between chitosan andα -tocopherol. Furthermore, the results from FTIR, NMR, and XRD spectroscopy confirmed electrostatic interactions between the two molecules. Overall, this procedure could be considered as a facile method to prepareα -tocopherol-loaded nanoparticles.